Water Hyacinth Nanocellulose addition effect on the Mechanical Properties of Sweet Potato Starch-Based Bioplastics - Milania Dwi Putri Mandasari; Samuel Budi Wardhana Kusuma (Universitas Negeri Semarang, 2023)
Environmental pollutionn that occurs is a problem that we must prevent in Indonesia. Factors causing enviromental pollution is plastic waste. This factor encourages the utilization of natural raw materials such as starch and nanocellulose in manufacture of biodegradable. The purpose of this research was to determine the effect of the addition of nanocellulose on the mechanical properties of bioplastics. The results of the synthesis of nanocellulose water hyacinth stems through acid hydrolysis and sonication obtained a particle size of 279.8 nm. The results of testing the mechanical properties with the addition of 0%, 10%, 15%, 20%, and 25% nanocellulose showed that the tensile strength and elongation values increased with each of the highest values obtained by sample D nanocellulose 25% of 4.96 MPa and 80,80%. However, the elastic modulus results obtained were irregular values and the highest value was obtained by sample A nanocellulose 10% of 6.62%. The results of the biodegradation rate showed that the higher the concentration of nanocellulose, the lower the biodegradation rate, the highest value obtained by sample A was 60.34%. Based on the mechanical properties, it was shown that the best results were obtained for sample D. The best results, morphological tests were carried out which showed poor distribution of nanocellulose filler due to agglomeration in certain areas.